Biodegradation of Organic Waste Using Bacillus Species Isolated From Soil - Rana Chhetri, Bibek; Silwal, Preksha; Jyapu, Pooja; Maharjan, Yumika; Lamsal, Trishana; Basnet, Anup (International Journal of Applied Sciences and Biotechnology, 2022)
Organic waste can be enzymatically degraded by microbes. In this study, the Bacillus species were isolated from soil and identified as Bacillus subtilis, Bacillus licheniformis, Bacillus macquariensis, Bacillus brevis, and Bacillus circulans which were optimized considering pH (5, 7, 9) and temperature (37°C, 45°C, 55°C) for the maximum production of amylase, gelatinase, lipase, and cellulase, principally for the degradation of organic waste. The maximum production of amylase was found at 37°C with pH 7 and 9, gelatinase and lipase at 37°C with pH 5,7,9 by almost all identified species. Similarly, the production of cellulase was shown by Bacillus licheniformis only at 45°C, pH 5. The degradation was confirmed by the analysis of the solid content of degraded waste. The maximum degradation of starch and lipid-containing waste was shown by Bacillus macquariensis whereas Bacillus circulans were able to degrade gelatin-containing waste effectively. Bacillus species showed a synergistic effect in biodegradation. Bacillus subtilis and Bacillus licheniformis used in ratios 1:1 and 1:2 were found to be effective degraders of lipid and starch-containing waste respectively. Bacillus macquariensis, Bacillus brevis, and Bacillus circulans used in ratio 1:1:1 showed effective degradation of gelatin-containing waste. The degradation of the organic waste by multi-enzyme producer Bacillus species can be the most effective and eco-friendly method and their optimization for enzyme production can be beneficial for commercial enzyme production as well as for biotechnological applications.Int. J. Appl. Sci. Biotechnol. Vol 10(2): 104-111.